The Impact of Yoga on Cancer Survivorship: A Scoping Review - Giridharan, S; Shanbhag, Nandan; Pandiyan, Bhuvana (International Research Journal of Ayurveda & Yoga, 2024)
Background: As cancer survival rates improve, survivors face numerous physical and psychological challenges. Yoga, an ancient practice integrating physical, mental, and spiritual health, has shown potential in alleviating cancer treatment-related symptoms and enhancing overall health. Methods: This scoping review conducted a comprehensive literature search across multiple databases, focusing on randomized trials that assessed yoga’s effects on cancer survivors post-treatment. The review spanned studies published between 2018 and 2022, emphasizing physical and psychosocial benefits. Results: Eight randomized trials were identified, demonstrating yoga’s diverse benefits across physical and psychological dimensions. Significant findings include reductions in depression, improvements in shoulder mobility, pain, and anxiety, management of cancer-related fatigue, sleep quality, and modulation of inflammatory cytokine profiles, suggesting holistic benefits in managing cancer side effects. Conclusion: Yoga presents a holistic, low-risk intervention that significantly improves quality of life, manages fatigue, and supports psychological well-being in cancer survivors. Future research should investigate yoga’s therapeutic potential and develop personalized interventions for survivors’ recovery and long-term well-being.